Zechariah's Horse Visions and Angelic Intermediaries: Translation, Allusion, and Transmission in Early Judaism - Allen, Garrick V. (The catholic biblical quarterly, 2017)
In this article, I examine the interplay of transmission and exegesis in Zechariah's textual history, analyzing the strategies that early interpreters employed to create coherence in a difficult text. I use Zechariah's horse visions as examples, exploring their presentation in the early versions and the Book of Revelation. The following examination explores the form of Zechariah used by these ancient interpreters and the habits of reading that are implied in their presentation of reused material. The evidence suggests that, by the late Second Temple period, the majority of readers conceptualized Zech 1:8 and 6:1-5 as coreferential visions and that this linking was representative of a larger strategy of coherence. This strategy is also part of a wider tradition of correlating Zechariah's horses with other heavenly figures in the Hebrew Bible, a tradition that is most prevalent in Targum Jonathan.